2002
DOI: 10.1037/0022-006x.70.4.976
|View full text |Cite
|
Sign up to set email alerts
|

A finite mixture model of growth trajectories of adolescent alcohol use: Predictors and consequences.

Abstract: The current study sought to identify classes of growth trajectories of adolescent alcohol use and to examine the predictors and outcomes associated with the classes. Alcohol use was assessed from Grades 7 to 12 in a school-based sample. Latent growth mixture modeling was used, and results indicated 5 discrete longitudinal drinking patterns. The 2 most common drinking patterns included occasional very light drinking from Grades 7 to 12 and moderate escalation in both quantity and frequency of alcohol use. One g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
203
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(231 citation statements)
references
References 32 publications
24
203
1
3
Order By: Relevance
“…This is consistent with Bennett et al (1999), who found that escape and enhance reasons for use were greatest for the persistent and developmentally limited drinking groups. The effects for negative affect were less robust, supporting previous work showing this to be a weaker predictor than is behavioral undercontrol (e.g., Colder et al, 2002).Consistent with cross-sectional analyses of our own data (Sher et al, 1991), we expected to see the strongest effect of family history on more problematic measures of alcohol involvement. We did, in fact, find a difference between chronic and nondiagnosing groups for AUD and alcohol dependence.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with Bennett et al (1999), who found that escape and enhance reasons for use were greatest for the persistent and developmentally limited drinking groups. The effects for negative affect were less robust, supporting previous work showing this to be a weaker predictor than is behavioral undercontrol (e.g., Colder et al, 2002).Consistent with cross-sectional analyses of our own data (Sher et al, 1991), we expected to see the strongest effect of family history on more problematic measures of alcohol involvement. We did, in fact, find a difference between chronic and nondiagnosing groups for AUD and alcohol dependence.…”
supporting
confidence: 87%
“…Most of the correspondence was due to concordance between corresponding groups, although, at times, there was a tendency for the chronic group to be classified as developmentally limited or later onset. Bennett et al, 1999;Chassin et al, 2002;Colder et al, 2002;Hill et al, 2000;Stice, Myers, & Brown, 1998;Tucker et al, 2003;Wills et al, 1996). Substance use such as drinking may occur in the context of general problem behavior, whereby behavioral undercontrol and substance use are two of a number of behaviors associated with a deviant lifestyle (Farrell, Danish, & Howard, 1992;Jessor & Jessor, 1977).…”
Section: Agreement Across Alternate Indices Of Alcohol Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications of GGMM have also distinguished classes based on growth factor means only (e.g., Colder et al, 2002;Tucker et al, 2003). Although Li et al (2002) were able to model growth factor variances across class, their model was limited to two classes, which is a relatively simple analytic model.…”
Section: Analytic Proceduresmentioning
confidence: 99%
“…In addition, given the large sample size (which affects values of AIC and BIC), we considered three other criteria: class prevalence (we tended not to consider classes that included less than 5% of the sample as they were unlikely to be replicable), class interpretability (the extent to which an additional class provided unique information) and stability (the extent to which the nature and prevalence of the classes changed when demographic variables were controlled) See Colder et al (2002) for a more extended explanation of these criteria. We noted significant variability around the mean for the intercept and slope factors, suggesting individual differences and the likelihood of distinct classes of heavy drinkers and smokers over the observation period.…”
Section: Mixture Modeling: Extracting Trajectoriesmentioning
confidence: 99%